Perinatal outcomes of renal transplant pregnancies: a 22-year experience at a single tertiary referral center. (1st September 2020) - Hortu, Ismet; Arı, Sabahattin Anıl; Akdemir, Ali; Koroglu, Ozge Altun; Yılmaz, Mumtaz; Toz, Huseyin; Sagol, Sermet; Ergenoglu, A. Mete
Abstract: Background: Renal transplantation not only prolongs survival but also improves quality of life and fertility, particularly in patients with end-stage renal disease. The aim of this study was to evaluate the renal and perinatal outcomes of pregnancy after renal transplantation at a high volume academic tertiary hospital. Methods: Fifty-one renal transplant patients (RTPs) who experienced pregnancy after transplantation and received care at Ege University Hospital between January 1995 and December 2017 were retrospectively identified. Data on demographics, comorbidities, and clinical perinatal outcomes were analyzed. Results: The median age of expectant mothers with renal transplantation was 30.51 ± 5.28 years (range 23–41). The mean interval between discontinuing birth control methods and the last menstrual period was 22 months. Preeclampsia occurred in six pregnancies (11.5%), and 43 of 52 pregnancies resulted in live births (82.6%). The mean gestational age at birth was 36.35 ± 2.36 weeks (range: 26–38). A total of 15 births were preterm deliveries (28.8%). Intrauterine growth retardation (IUGR) was detected in four cases. The mean birth weight was 2664.58 ± 613.99 g (range: 600–3.800 g). Twelve newborns were hospitalized in the neonatal intensive care unit (23%). A significant inverse correlation between birth weight and preconception serum creatinine level was found ( p < .001; r = −0.532). An inverse correlation between the interval between transplantation and pregnancy and low postpartum serum creatinine level was established significantly ( p < .05; r = −0.331). In addition, an inverse correlation between preconceptional serum creatinine and postpartum serum creatinine in the first year was found statistically significant ( p < .001, r = −0.681). Conclusion: Even though pregnancy does not seem to adversely affect renal graft function, risks of perinatal as well as obstetrical complications should not be ignored. Pregnancies in RTPs should be followed closely by a multidisciplinary team of experts to minimize perinatal complications before and during pregnancy.